SOSIALISASI PEMANFAATAN QRIS SEBAGAI TRANSAKSI DIGITAL KEPADA PELAKU UMKM DI WILAYAH PASAR MUARA BUNGO - Mahendra, Rafly; Mustin, Wizeadly; Ramadhan, Anggun Bunga; Yudika Bungaran, Kevin; Yudi Saputri, Bella; Yosefri Yanti, Vivi (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
This service aims to find out the impact of socialization of the use of QRIS as a digital transaction to MSME actors in the Muara Bungo market area. The service method used is observation, namely by observing and recording the behavior, attitude, and response of MSME actors to QRIS before and after socialization. The data collected includes the number of transactions, frequency, and value of transactions using QRIS, as well as the level of satisfaction and difficulties of MSME actors in using QRIS. The results of the study show that the socialization of the use of QRIS as a digital transaction has a positive effect on MSME actors in the Muara Bungo market area. This can be seen from the increase in the number of transactions, frequency, and value of transactions using QRIS, as well as the level of satisfaction and reduction in the difficulty of MSME actors in using QRIS. This service provides recommendations for related parties to increase socialization and facilitation of the use of QRIS as a digital transaction to MSME actors in other regions, as well as overcome the obstacles still faced by MSME actors in using QRIS.